FAKTOR - FAKTOR YANG MEMPENGARUHI MENURUNNYA JUMLAH KUNJUNGAN WISATAWAN KE KAWASAN PARIWISATA LOVINA DI KABUPATEN BULELENG - Nyoman Danendra Putra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The rapid development of tourism facilities in the Lovina Tourism area and the decline in the number of tourist visits to that area causing several impacts such as the number of hotels and restaurants loss, the issue of shifting the hotel market from foreign tourists to local people. The research objective is to determine the factors that influence the decline in tourist visits to the Lovina Tourism Area and actions that need to be taken in order to increase tourist visits. Data is collected through discussion groups, observations, and interviews. Sampling is through group discussions and interviews. In analyzing problems and research results, quantitative descriptive analysis is used. The results showed that the decline in the number of tourist visits to the Lovina Tourism Area was caused by the condition of Bali tourism in general and the condition of Lovina tourism in particular such as: 1) excessive public behavior in offering services to tourists, 2) great distances from tourist centers at Bali, 3) Inadequate accommodation facilities, 4) The potential of the attraction has not been managed optimally and professionally, 5) promotions carried out by tourists and the government are very necessary to be increased and to choose promotional channels that are in accordance with the current conditions.The government is expected to arrange tourism facilities to create an attraction for the Lovina Tourism Area and carry out an integrated promotion between the government and tourism actors to increase the number of tourist visits to the Lovina Tourism Area. Keyword: Lovina Tourism area, tourism facilities, tourist visits